Rapid and effective processing of blood specimens for diagnostic PCR using filter paper and Chelex-100. - Polski, J M (1998)
AIM: To provide a more efficient method for isolating DNA from peripheral blood for use in diagnostic DNA mutation analysis. METHODS: The use of blood impregnated filter paper and Chelex-100 in DNA isolation was evaluated and compared with standard DNA isolation techniques. RESULTS: In polymerase chain reaction (PCR) based assays of five point mutations, identical results were obtained with DNA isolated routinely from peripheral blood and isolated using the filter paper and Chelex-100 method. CONCLUSION: In the clinical setting, this method provides a useful alternative to conventional DNA isolation. It is easily implemented and inexpensive, and provides sufficient, stable DNA for multiple assays. The potential for specimen contamination is reduced because most of the steps are performed in a single microcentrifuge tube. In addition, this method provides for easy storage and transport of samples from the point of acquisition.